1963
DOI: 10.1590/s0006-87051963000100059
|View full text |Cite
|
Sign up to set email alerts
|

Adubação da cana-de-açúcar: IX - Experimentos preliminares com micronutrientes

Abstract: Neste trabalho são apresentados os resultados obtidos era três experimentos para verificar possíveis deficiências de micronutrientes e de magnésio em solos tipos terra-roxa-misturada e massapê-salmourão, cultivados há mais de quinze anos com cana. Foram feitas aplicações de sulfato ferroso, tetraborato de sódio, sulfato de magnésio, sulfato de manganês, sulfato de cobre, sulfato de zinco e molibdato de amônio, nos sulcos de plantio, na presença de NPK. Nos solos massapê-salmourão, os micronutrientes boro, moli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Andrade et al (1995), in an experiment with fritted trace elements-FTE (ground silicate oxides) and soluble sources of B (borax), Cu (copper sulfate) and Zn (zinc sulfate) application, verified that both joint application (FTE) as well as isolated micronutrients application did not result in increases in TSS. Older studies also did not show increases in TSS yield due to the Zn fertilization (Alvarez and Wutke 1963;Alvarez et al 1979). However, Mellis et al (2009), evaluating the micronutrients application in sugarcane in eight locations in Brazil, observed, in four sites, an average increase of 29% in TSS yield of the plant cane with the application of 3 kg ha -1 of Zn in the planting furrow.…”
Section: Yield Parameters and Technological Attributes Of Sugarcane Imentioning
confidence: 96%
“…Andrade et al (1995), in an experiment with fritted trace elements-FTE (ground silicate oxides) and soluble sources of B (borax), Cu (copper sulfate) and Zn (zinc sulfate) application, verified that both joint application (FTE) as well as isolated micronutrients application did not result in increases in TSS. Older studies also did not show increases in TSS yield due to the Zn fertilization (Alvarez and Wutke 1963;Alvarez et al 1979). However, Mellis et al (2009), evaluating the micronutrients application in sugarcane in eight locations in Brazil, observed, in four sites, an average increase of 29% in TSS yield of the plant cane with the application of 3 kg ha -1 of Zn in the planting furrow.…”
Section: Yield Parameters and Technological Attributes Of Sugarcane Imentioning
confidence: 96%
“…Probably, the interaction between the different sources of micronutrients applied reduced the availability of Zn and B to the plants, whereas yield responses were observed after separate applications. Alvarez & Wutke (1963) and Andrade et al (1995) observed no significant yield responses either after the application of micronutrient mixtures.…”
Section: Resultsmentioning
confidence: 95%
“…As respostas à aplicação de micronutrientes em cana-de-açúcar têm sido pouco frequentes, como já mostravam os trabalhos pioneiros de Alvarez & Wutke (1963), Espironelo (1972, Alvarez et al (1979), entre outros, entretanto, aumentos de produção de colmos em função da aplicação de micronutrientes têm sido relatados esporadicamente (ALVAREZ & WUTKE, 1963;AZEREDO & BOLSANELLO, 1981;MARINHO & ALBUQUERQUE, 1981;ALVAREZ, 1984;CAMBRIA et al,1989;ORLANDO FILHO et al, 2001;FRANCO et al, 2008). Tendo em vista a falta de informação no que diz respeito à influência dos micronutrientes na cana-de-açúcar, justifica-se a inclusão dos micronutrientes nas análises de solos para futura averiguação de suas influências individualmente ou em conjunto na produtividade e qualidade da cana-de-açúcar.…”
Section: Trabalhos Como O Deunclassified